DESIGNING MACROTENSE AS TEACHING MULTIMEDIA IN TALKING ABOUT DAILY ACTIVITY AND GENERAL TRUTH - Nadir, Moh. Ridwan; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aims to design flash application as teaching multimedia in learning talking about daily activity and general truth. The topic was taken based on the syllabus that was being used in the school. The method of this research is development research using ADDIE instructional design (Analyzing, Designing, Developing, Implementing, and Evaluating) as the phases in designing MacroTense. MacroTense is a flash application containing materials about the topic that is talking about daily activity and general truth. MacroTense provides four menus as the main features. The menus are main lesson, video lesson, quizzes, and extras. Each menu presents different types content regarding the topic with complete animation and narration. Assessment rubric of MacroTense results 30 points of range score 0-44 to indicate MacroTense as Satisfactory. Meanwhile the questionnaire results 87.5% that indicate MacroTense as very good/feasible to be used as teaching multimedia. Therefore, the researcher suggests the using of MacroTense is good to encourage the students’ motivation in learning the topic. Keyword: Flash Application, ADDIE Instructional Design. Abstrak: Penelitian ini bertujuan untuk merancang aplikasi flash sebagai perangkat multimedia dalam topik pembelajaran Talking about Daily Activity and General Truth. Topik itu diambil berdasarkan silabus yang sedang digunakan di sekolah. Metode penelitian ini adalah penelitian pengembangan menggunakan ADDIE desain instruksional (Menganalisis, Merancang, Mengembankan, Menerapkan, dan Mengevaluasi) sebagai fase dalam merancang MacroTense. MacroTense adalah aplikasi flash yang berisi materi tentang topik Talking about Daily Activity and General Truth. MacroTense menyediakan empat menu sebagai fitur utama. Menu pelajaran utama, pelajaran video, kuis, dan ekstra. Setiap menu menyajikan berbagai jenis konten mengenai topik dengan animasi lengkap dan narasi. Rubrik penilaian MacroTense menghasilkan 30 poin dari rentang skor 0-44 untuk menunjukkan MacroTense sebagai Memuaskan. Sementara kuesioner menghasilkan 87,5% yang menunjukkan MacroTense sebagai sangat baik / layak untuk digunakan sebagai multimedia pembelajaran. Oleh karena itu, peneliti menyarankan penggunaan MacroTense baik untuk mendorong motivasi siswa dalam belajar topic tersebut.   Kata Kunci: Aplikasi Flash, ADDIE Desain Instruksional